In-Vitro Effect of Casein Phosphopeptide Amorphous Calcium Phosphate on Enamel Susceptibility to Staining by Tea during Bleaching Treatment - Homayoom Alaghemand; Sedighe Sadat Hashemi Kamangar; Nafiseh Zarenegad; Negin Tabari; Hoorieh Abedi; Soraya Khafri (Tehran University of Medical Sciences, 2016)
Objectives: Bleached enamel is more susceptible to staining, and application of remineralizing agents may decrease enamel susceptibility to staining. This study sought to assess the effect of casein phosphopeptide amorphous calcium phosphate (CPP-ACP) on enamel susceptibility to staining during bleaching treatment. Materials and Methods: Forty central and lateral incisors and first premolar teeth were evaluated in four groups of 10. Group one specimens were subjected to in-office bleaching. Group two underwent in-office bleaching followed by surface treatment with CPP-ACP. Group three specimens received home bleaching and group four underwent home bleaching followed by CPP-ACP surface treatment. After each course of daily bleaching, specimens were immersed in tea solution. Home bleaching (15% carbamide peroxide) was performed for 14 days and in-office bleaching (40% hydrogen peroxide) was carried out in two sessions with an eight-day interval. The color of specimens was analyzed at baseline and post-intervention using EasyShade Shade-Selection Device. Two-way ANOVA was used to evaluate the effects of bleaching type and surface treatment on color change. Then, the means were compared by Tukey's HSD test (P=0.05). Results: The interaction effect of surface treatment and type of bleaching was not significant on any color parameter (P>0.05). Surface treatment had significant effects on ΔL (P=0.004). Type of bleaching had a significant effect on "b" parameter (P=0.00). The effect of bleaching type on ΔE was significant (P=0.00) but the effect of surface treatment was not (P=0.34). Conclusion: CPP-ACP had no significant effect on preventing enamel staining by tea during bleaching treatment.